2021
DOI: 10.3126/njz.v5i1.38281
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasites among children attending outpatient department of Kanti Children’s Hospital, Kathmandu, Nepal

Abstract: Intestinal parasitic infection is one of the main causes of morbidity and mortality in developing countries, especially among children. Even minimum infection of parasites in children may have negative effects on growth, iron deficiency anemia, perceiving function, and impaired cognition. The main objective of this study was to determine the prevalence of intestinal parasites and associated factors among the children attending the Outpatient Department of Kanti Children’s Hospital, Kathmandu for various illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The highest infection of females by intestinal parasites found in the present study is not in agreement with the finding reported by Mohammed [21], in which intestinal parasites were more prevalent between the male patients (65.7%) than the females (57.4%). Nevertheless, this finding is in line with Acharya et al [22] whose study indicated the highest prevalence of parasitic infection in females (32.11%) as compared with the males (21.99%). Moreover, Patel et al [23] and Zemene and Shiferaw [24] reported similar results in their study with predominance of parasitic infection in females.…”
Section: Journal Of Parasitology Researchsupporting
confidence: 91%
“…The highest infection of females by intestinal parasites found in the present study is not in agreement with the finding reported by Mohammed [21], in which intestinal parasites were more prevalent between the male patients (65.7%) than the females (57.4%). Nevertheless, this finding is in line with Acharya et al [22] whose study indicated the highest prevalence of parasitic infection in females (32.11%) as compared with the males (21.99%). Moreover, Patel et al [23] and Zemene and Shiferaw [24] reported similar results in their study with predominance of parasitic infection in females.…”
Section: Journal Of Parasitology Researchsupporting
confidence: 91%
“…Due to a lack of health, inadequate sanitation, poor hygiene practices, and poor health education, the problem of intestinal parasite infection in outpatients remains a critical public health concern because they are among the primary causes of sickness and death globally. According to current estimates, at least a quarter of the world's population is chronically infected with intestinal parasites, with the vast majority of those affected living in developing nations ( 7 9 ). Intestinal parasite infections are frequent in the tropics, causing severe public health issues in underdeveloped nations ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, they represent physical vouchers that retain the diagnostic characters underlying the description of a new taxon. In addition to being the reference for a sci-entific name, they also serve as a scientific memory for later research (Acharya and Subedi 2005).…”
Section: Introductionmentioning
confidence: 99%